The influence of tourist evaluative factors on tourist behavioral intention: the mediating role of tourist satisfaction - Elmer Hafiizh Fernaldi; I Made Sukresna (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2018)
This study examines the effect of tourist evaluative factors, specifically service quality and tourist experience on tourist satisfaction and its further influence on revisit intention and intention to recommend. Service quality and tourist experience serve as independent variables, while revisit intention and recommend intention are posited as dependent variables, with satisfaction acts as the intervening variable. Data analysis using Structural Equation Modeling (SEM) of 186 tourist visiting Umbul Sidomukti, Semarang, Central Java, Indonesia, finds that both revisit intention and intention to recommend could be increased through the improvement of service quality and tourist satisfaction.